If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = (400 + 20x)(90 + -2x) Multiply f * x fx = (400 + 20x)(90 + -2x) Multiply (400 + 20x) * (90 + -2x) fx = (400(90 + -2x) + 20x * (90 + -2x)) fx = ((90 * 400 + -2x * 400) + 20x * (90 + -2x)) fx = ((36000 + -800x) + 20x * (90 + -2x)) fx = (36000 + -800x + (90 * 20x + -2x * 20x)) fx = (36000 + -800x + (1800x + -40x2)) Combine like terms: -800x + 1800x = 1000x fx = (36000 + 1000x + -40x2) Solving fx = 36000 + 1000x + -40x2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 36000x-1 + 1000 + -40x Simplifying f = 36000x-1 + 1000 + -40x Reorder the terms: f = 1000 + 36000x-1 + -40x
| 137.8=3.14r^2 | | 24x-40=20x-40 | | 8/2s^-3 | | 135=16x^2+110x+5 | | (3a-6g)(3a+5g)=0 | | x+2y=18.5 | | 8x-4.25=86 | | 5(2-6n)=70 | | 2(x+14)+(2x+-14)= | | -6n=24-14n | | 3+6y=4+8y | | 35x-5y=2.7 | | 2.333333333333333333333333333333333333333333y=84 | | X(x^2+7x)=-60 | | 3q^2-6q=2q^2-8q+63 | | 3t/5=5 | | 7(x-1)=3x+13 | | 3x-5y=2.5 | | 2k^2-13k-24= | | 3.2/8 | | y=9(1)+3 | | x+100=43 | | 3x^2/y | | 6=x/(3-x) | | 6x^2-8y=-3 | | x=-16y^2+64y+30 | | (8e^2+5e+1)-(8e^2+5)=8e+7 | | (-3)/(6) | | 9x-7=5x+25 | | 0.167=(x)/(0.1497-x) | | x*20=4 | | 2x+7x-12+4x+4x+2+5x=540 |